PRESENTATION-PRACTICE-PRODUCTION METHOD ON THE LEARNING OUTCOMES OF WRITING PROCEDURE TEXT - Batubara, Muhammad Hasyimsyah; Srikandi, Cut Novita; Anwar, Mar’ah Sophiyah (Jurnal As-Salam, 2023)
This research destination is to determine the effectiveness of the PPP methods in improving the ability to write procedural texts for learning English. The students of class X SMK N 3 Takengon are the population. The sampling technique used by the researcher is divided into two groups: The researcher made classes X TKJ 1 as many as 28 students as an experimental class and X TKJ 2 as many as 28 as the control class. This research is designed with an experimental study in a quantitative method approach. The researcher used observation and tests (pre and post-test) to gather data. After the test was conducted, the next stage was the validity, reliability, hypothesis, and N-Gain tests. Based on statistical calculations, the score Tscore is higher than the Ttable (33.51 > 1.67). The N-Gian test is 0.9 in the experimental and 0.8 in the control classes. Ultimately, the study hypothesis (Ha) is accepted and indicates that the hypothesis (Ho) is rejected. It concluded that applying the PPP method ascertainable affects the ability to write procedural texts for research samples.